The Impact of Good Corporate Governance, Internal Controls, and Human Resource Competence on Fraud Prevention (A Case Study at PT Britania Akademi Indonesia): Pengaruh Good Corporate Governance, Pengendalian Internal dan Kompetensi Sumber Daya Manusia terhadap Pencegahan Fraud (Studi Kasus pada PT Britania Akademi Indonesia) - Fanny; Frenky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to determine whether Good Corporate Governance, Internal Control and Human Resource Competence have a significant effect on Fraud Prevention (Case Study at PT Britania Akademi Indonesia). This study uses quantitative data methods and the data source is primary data. The population in this study were all admin staff and teachers working at PT Britania Akademi Indonesia, totaling 33 people. The sample of this study amounted to 33 people obtained by saturated sampling technique. Data analysis and testing consisted of validity test, reliability test, descriptive statistics, classical assumption test, multiple linear regression analysis, partial (t-test) and simultaneous (F-test) hypothesis testing, and coefficient of determination test. The results showed that Good Corporate Governance had a significant effect on Fraud Prevention with a t-value of -2.502 > t-table 2.048. Internal Control had a significant effect on Fraud Prevention with a t-value of 3.430 > t-table 2.048. Human Resource Competence had a significant effect on Fraud Prevention with a t-value of 8.368 > t-table 2.048. Good Corporate Governance, Internal Control, and Human Resource Competence have a significant simultaneous effect on Fraud Prevention with a calculated F value of 83,000 > Ftable 3.34 with a regression coefficient value of 88.5%.